The Effect of Rewards and Punishments on Teacher Performance - Reihan Yudha Permana; Irawati Irawati; Rini Setyaningsih (Journal of Educational Management Research, 2025)
This study aimed to examine the effect of rewards and punishments on teacher performance. The research involved 32 teachers, with data collected through questionnaires and documentation. The study used quantitative methods, including multiple linear regression analysis. Results indicated that rewards had a positive and significant effect on teacher performance (sig. 0.009 < 0.05), while punishments showed no significant effect (sig. 0.598 > 0.05). Both variables combined explained 32.1% of the variation in teacher performance (R² = 0.321). The theoretical implications suggest that reward mechanisms, as a form of positive reinforcement, are crucial in enhancing teacher motivation and performance, aligning with Skinner's reinforcement theory. The practical implications point to the importance of schools developing more varied and consistent reward systems while carefully managing punishments to avoid negative impacts on teacher morale. This study contributes new empirical evidence to the understanding of reward and punishment systems in public Islamic schools, providing insights into improving teacher motivation and performance through effective incentive management.